Bahasa Inggris - Feny Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2023)
The Ginkgo biloba plant is the only living species in the division of Ginkgophyta. It is also known as the maidenhair tree. The uniqueness of Ginkgo biloba lies in its fan-shaped leaves. The color and shape of Ginkgo biloba have been adapted into a performance costume for the prestigious Met Gala Party. This article discusses the design of the stage costume using Ginkgo biloba as a source of metaphor in fashion with adaptation techniques. The method used involves designing fashion products, starting from creating a concept, and mood board, making several alternative designs, and product prototypes. The resulting product is a Ginkgo biloba metaphor visualized in the form of fashion silhouettes, colors, accessories, and decorative details in the form of knife pleats. Respondent’s response to the metaphor through the adaptation technique of the Ginkgo biloba leaf shape is that almost all respondents can capture it well in the form of accessories, knife pleats, and silhouettes. However, the metaphor through the adaptation technique of the pattern arrangement, less than half of the respondents can capture it. In terms of color, almost all respondents can capture the color metaphor in the monochromatic scheme of the basic yellow color as the source of color ideas from Ginkgo biloba.